'Around the Meeting Tree': methodological reflections on using digital tools for research into Indigenous adult education in the Networking Tranby project. Issue 1 (2nd January 2019) - Goodall, Heather; Norman, Heidi; Russon, Belinda
ABSTRACT: The authors reflect on the methodology of using digital tools to learn about the experiences of Indigenous people enrolled from 1980 to 2000 as adult students at Tranby, an Indigenous-controlled post-secondary college. This collaboration between Tranby and the University of Technology Sydney drew on debates in post-colonial studies, oral history and archival studies. The authors found that participants prioritised personal control in all social media communication and engaged most actively in person-to-person communication to take part in this research. Participants were eager to share memories of student experiences but they have preferred to contribute to online publications which focused on activities, rather than on individuals. To support participants' desire for control over digital communication, the authors slowed the pace of online outcome development to allow flexible and ongoing consent arrangements along with non-custodial approaches to oral, archival, photographic and material collections.